The Microfoundations of Bureaucratic Outcomes: Causes and Consequences of Interpretive Disjuncture in Eviction Cases. (3rd December 2019) - Nelson, Kyle
Abstract: Eviction transforms landlords into plaintiffs and tenants into defendants, reframing expansive histories of housing trouble into legal problems. Researchers note high rates of default judgments against tenants, a majority of tenants without attorneys, and a disconnect between the ways that landlords and tenants understand cases. This study reveals the micro-foundations of case outcomes by explaining causes and consequences of "interpretive disjuncture." How does interpretive disjuncture shape case trajectories and outcomes as housing trouble transforms into an eviction lawsuit? Drawing on one year of ethnographic fieldwork in tenants' rights clinics in Los Angeles County, I follow tenants' cases back to their roots and explain how both everyday and institutional challenges shape tenants' interpretive processes as they navigate eviction.